Prismatic Blade Production at the Sinclair Site, Tennessee: Implications for Understanding Clovis Technological Organization. Issue 3 (July 2022) - Tune, Jesse W.; Jennings, Thomas A.; Deter-Wolf, Aaron
Abstract : The Tennessee Division of Archaeology documented an extensive Paleoindian lithic quarry and workshop at the Sinclair site in Tennessee in 2008. We present the first detailed description of the lithic assemblage here, which focuses on aspects of its prismatic blade technology. Quantitative and qualitative attributes of 117 blades are assessed to characterize the assemblage and investigate human behaviors related to its formation. We then compare the blades from Sinclair to other blade assemblages. Blades at Clovis workshop sites are large and generally unstandardized. Mobile Clovis bands selected long, highly standardized blades from workshop sites, cached them as resource insurance, and crafted and used them as tools at campsites. The prismatic blade assemblage at Sinclair and other sites throughout the Midsouth suggests that this region played an important role in the development of prismatic blade technology at the end of the Pleistocene.